CHANGES IN THE BILE-ACIDS COMPOSITION OF BILE JUICE AFTER FAT INTAKE - CRISTINA DINU; CRISTIANA DIACONESCU; N. AVRAM; D. CUCĂ (Scientific Papers Animal Science and Biotechnologies, 2023)
A high fat intake increases the flow of bile or changes the composition of bile acids in refluxed duodenal contents, and then plays an important role in the developmental precancerous lesion of BE and leading to esophageal adenocarcinoma EAC. Wistar rats were divided into three groups based on their diet: a control group (fed with standard diet, containing 4.20% soybean oil), a second group (fed with a low cowfat diet, containing 4.20% cow fat) and the third group (fed with a high cow-fat diet, containing 16.8% cow fat). The TCA value detected in the animals fed the high cowfat diet (median concentration, 13.8 ± 2.42 mmol/L) was significant increased comparative with those detected of animals fed the standard diet (8.15 ± 1.22 mmol/L). The TDCA value in the high cow-fat group (2.64 ± 0.97 mmol/L) was significantly increased comparative with those detected of animals fed the standard diet (1.66 ± 0.50 mmol/L).